Agrifood systems' resilience for sustainable food security amid geopolitical tensions: a systematic literature review - Mkumbukiy, Ally; Loghmani-Khouzani, Taha; Madani, Kaveh; Guenther, Edeltraud (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study examines the resilience of the agrifood systems amid geopolitical tensions with a primary focus on the Ukraine-Russia war and its increased effects on global food security, climate change, and post-pandemic recovery. The study explores different resilience elements, scenarios, and behaviors of agrifood systems, highlighting how geopolitical conflicts disrupt resource availability and economic stability. Further, it explores the existing Resource Nexus and its influence on sustainable food and nutrition security amid geopolitical tension. Much research focuses on agrifood systems' resilience in the context of climate change and pandemics, repeatedly overlooking the impacts of geopolitical tensions and related policies enacted for sustainable food security.MethodsFocused on geopolitical tension as an influence on food security, 76 articles were systematically reviewed to identify key resilience elements and scenarios enacted based on countries' development, discovered major vulnerability indicators, and Resource Nexus of agrifood systems.ResultsThis review leads to the identification of four key resilience scenarios of the agrifood system amid geopolitical tensions: fragility reduction, robustness building, adaptive strategies, and transformative change over time. In general, the reduction of agrifood system fragility was more prevalent compared to the other three scenarios. There was a decline in the agrifood system's performance due to the existence of some policies that increased the system's instability over time. The study further identifies that the impact of enacted resilience policies on sustainable food security is not uniform. It often influences positive or negative outcomes depending on its feedback nature at different operational levels of the agrifood system. During geopolitical tensions, food, energy, and finance are the most affected sectors, followed by other interconnected resources such as land, water, food (LWF), and water, energy, and food (WEF).DiscussionIn the presence of effective policies and scenarios, the agrifood system experiences improved resilience and sustainability that contribute to the beneficial relationship between resources, and all pillars of food security.